Implementasi Pembelajaran Berdiferensiasi Berbasis Profil Gaya Belajar Peserta Didik pada Mata Pelajaran Bahasa Indonesia Kelas XI E di SMAN 1 Gerung - Buah Hati; Siti Rohana Hariana Intiana; Pipit Aprilia Susanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the implementation of differentiated instruction based on students’ learning style profiles in Indonesian language learning for Class XI E at SMAN 1 Gerung and to identify the challenges faced by teachers in its implementation. This research employed a descriptive qualitative approach to provide an in-depth description of differentiated instruction in classroom learning. The subjects consisted of 35 students, one Indonesian language teacher, and the vice principal for public relations. Data were collected through observation, semi-structured interviews, and questionnaires. Data validity was ensured through source and technique triangulation. Data analysis used the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings indicate that differentiated instruction has been implemented through preparation, implementation, and evaluation stages; however, its implementation has not been optimal. Teachers conducted diagnostic assessments, but the mapping of students’ learning styles was still not comprehensive. Differentiation in content, process, product, and learning environment tended to be uniform and had not fully accommodated students’ diverse learning needs. Evaluation was conducted through formative and summative assessment, although feedback had not been provided evenly to all students. The main challenges faced by teachers include limited time, facilities, learning media variation, and difficulties in designing learning activities and assessment instruments. Therefore, continuous teacher training and institutional support are needed to optimize differentiated instruction.